Studying the impact of the Syrian public sector economic indicators in economic development by using standard canonical correlation during the period (2000-2018). (Latakia University Journal - Economic and Legal Sciences Series, 2023)
In this research, we aim to modeling the relationship between the economic indicators in public sector, which are ( total government expenditure ,total government consumption, gross fixed capital formation and net foreign trade) and the selected indicators to shape economic development indicators which are (gross domestic product,  per capita gross domestic , inflation and exchange rate) depending on data published by the central bureau of statistic and central bank of Syria, we found that there is a relationship of statistical significance between the public sector economic indicators and economic development  in Syria. Show that the public sector economic indicators are mostly closely related to variables (gross domestic product, exchange rate, per capita gross domestic, inflation), and the variables of economic development are mostly closely related to variables  in public sector ( current expenditure, imports, investment expenditure , consumption expenditure, exports ).